Complete mitochondrial genome sequence of Gymnopilus junonius. Issue 3 (4th March 2021) - Cho, Sung Eun; Jo, Jong Won; Kwag, Young-Nam; Lee, Hyun; Chung, Jong-Wook; Oh, Seung Hwan; Kim, Chang Sun
Abstract: Gymnopilus junonius, a well-known poisonous mushroom, is distributed worldwide. It contains a hallucinogenic alkaloid psilocybin and several other bioactive compounds. The mitochondrial genome, a circular DNA molecule of 161, 145 bp, comprises 15 protein-coding genes, 24 transfer RNA genes, and 2 ribosomal RNA genes. The guanine-cytosine content was 31.56%. Based on the mitochondrial genome sequence, a phylogenetic tree was constructed to demonstrate the phylogenetic relationship. In this study, the phylogenetic positions of G . junonius and its related genera were determined.